THE INTERNATIONAL EXPERIENCE AND THE CURRENT RUSSIAN LEGISLATION REGARDING SUPERVISION OF MARGINAL CREDITING - E. S. Emelyanova (Стратегические решения и риск-менеджмент, 2020)
The article analyzes the international Supervisory experience of the European Union in terms of monitoring the implementation of short sales. The analysis was carried out in order to determine further key directions of development of the Russian market of margin lending. In addition, the article also considers the current Russian legislation in terms of supervision of unsecured transactions, regulated by the Decree of the Central Bank of the Russian Federation, which entered into force on July 1, 2019. The obtained results of the analysis allowed to make a comparative characteristic of the regulation of short sales in the European and Russian jurisdictions, as well as to make a forecast regarding the hypothetical transformations of the current Russian legislation.The analysis of the European experience in part of control of implementation of the short sales established by SSR to disclosure of information on short positions, to restrictions on short sales, to powers and ESMA obligations, etc., allows to come to conclusion that regulation in the Russian jurisdiction can be expanded not only due to complication of a procedure for granting of a marginal loan by inclusion in a portfolio of the client of difficult nonlinear tools, but also due to establishment of requirements for disclosure of information on the high-concentrated short positions and establishment of thus constantly reconsidered threshold size. In article the assumption that the designated directions of development of regulation of short sales regarding expansion of powers of the regulator also will increase transparency of intermediary activity and the financial market is made, having provided thus reliable protection of interests of clients of financial intermediaries.